Exploring neuro-mathematical connections in the resolution of a contextualized geometric problem - Cantillo-Rudas, Benilda Maria (Universitas Terbuka, 2025)
This study aims to explore the neuro-mathematical connections activated by high school and university students when solving a contextualized geometric problem. The urgency of this research lies in the need to deepen our understanding of the cognitive and neurological processes involved in mathematical problem-solving, particularly in spatial reasoning tasks. The theoretical framework combines Connections Theory and the Onto-semiotic Approach, focusing on the typology of neuro-mathematical connections. The qualitative, descriptive methodology was carried out in three phases: (1) selection of volunteer participants from high school and university levels; (2) data collection through the application of a geometric problem involving the volume of two boxes, with video recordings capturing students’ problem-solving processes; and (3) analysis using the theoretical framework to identify and interpret the neuro-mathematical connections activated during the task. The results revealed a rich network of cognitive processes encompassing mathematical practices, objects, processes, and semiotic functions. Specifically, students demonstrated: recognition of mathematical terms and symbols; activation of visual perception, spatial reasoning, and motor coordination; association of concepts and formulas; execution of intermediate calculations and unit conversions; sequential problem-solving; and reflective verification of results. These findings support the claim of the Extended Theory of Connections that connections are inherently cognitive processes. This research contributes to the field of mathematics education and cognitive science by providing an in-depth analysis of how students engage with mathematical problems through neuro-mathematical pathways. Future research should expand this work by incorporating neuroimaging or eye-tracking technologies to further validate and visualize the cognitive mechanisms underlying mathematical reasoning.